Studi Penggunaan Pektinase pada Pembuatan Sirup Mangga Kweni (Mangifera odorata Griff) - Khaerunisa, Sabbihisna; Astuti, Rahayu Dyah; Setyaningsih, Sundari (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2026)
This study aims to determine the optimal pectinase enzyme concentration and hydrolysis duration for the most preferred physical, chemical, and organoleptic characteristics of kweni mango syrup. The research was conducted from October 2024 to August 2025 at the Integrated Laboratory and Basic Science Laboratory of the Agricultural Institute (INTAN) Yogyakarta using a Completely Randomized Design (CRD) with a factorial pattern consisting of two factors and two replications. The first factor was the pectinase enzyme concentration (0%, 0.25%, 0.50%, and 0.75%), and the second factor was the hydrolysis duration (0, 30, and 60 minutes). Observation parameters included yield, vitamin C, viscosity, pH, total soluble solids, and organoleptic attributes. Data were analyzed using ANOVA at a 5% significance level followed by Duncan’s Multiple Range Test (DMRT). The results showed significant effects of both pectinase enzyme concentration and hydrolysis duration on yield, viscosity, total soluble solids, and organoleptic characteristics (color, taste, aroma, and overall acceptability), while no significant effects were observed on vitamin C content and pH. The best formulation was obtained using 0.50% pectinase enzyme concentration with a hydrolysis duration of 30 minutes.